Baranova S. V. Functional and semantic properties of the ordinal numerals - Baranova S. V. (Philological Treatises, 2020)
This article is devoted to the definition of the ordinal numerals in English. Their structural and semantic peculiarities are investigated. The functions of the ordinal numerals in the discourse are regarded. Different linguistic views of the problem are analysed. The place of the ordinal numerals in the conceptual and language spheres is defined.